Sodium Nitroprusside Functions in Browning Control and Quality Maintaining of Postharvest Rambutan Fruit - Zhang, Ruining; Yuan, Zhouyu; Jiang, Yuwei; Jiang, Fan; Chen, Ping (Frontiers in Plant Science, 2022)
Surface browning after harvest is the primary constraint affecting the storage life and market circulation of rambutans. In this study, rambutan fruits were soaked in sodium nitroprusside at different concentrations and stored at 25 ℃ for 8 d to explore the effects on postharvest quality and browning. The weight loss, browning index, and superoxide anion radical, hydrogen peroxide, and malondialdehyde contents of the treated fruits were reduced compared to those of the control fruits (soaked in distilled water). And fruits treated with sodium nitroprusside had a higher total phenolic content and lower polyphenol oxidase and peroxidase activity. In addition, compared with the control, the treated fruits exhibited higher phenylalanine ammonia lyase, ascorbate peroxidase, and superoxide dismutase activities; titratable acidity; and soluble solid, vitamin C, and protein contents, indicating high fruit quality. Overall, sodium nitroprusside treatment at 200 μmol L−1 demonstrated the most positive preservation effects. Therefore, sodium nitroprusside treatment, particularly at 200 μmol L−1, can be used as an eco-friendly, safe, and convenient method for postharvest quality management and high-efficiency preservation of rambutan fruits.